To Translate or Not to Translate in the Foreign Language Classroom? An Empirical-Experimental Study on Pedagogical Translation in Secondary Language Education - Schnell, Bettina; García Pérez, Carolina (Palgrave Macmillan (, Reino Unido), 2025)
.

Although it is commonly accepted that natural translation is an inherent aspect of bilingualism, in second language acquisition (SLA) and foreign language learning (FLL), pedagogical translation (PT) has been caught in the crossfire of language teachers, SLA researchers, and translation scholars. Since the advent of communicative language teaching, translation has been discouraged in foreign language classrooms, often based on limited empirical evidence. While there has been an increasing number of studies focusing on translation in foreign language teaching, the area remains under-researched. The present study aims to provide empirical evidence for the use of translation as a pedagogical tool in EFL secondary education classrooms. The rationale was to investigate the effectiveness of PT for early-stage learners of English (CEFR A2-B1) when compared to the standard communicative approach (CA). For this purpose, two grammar structures were chosen which are part of the first- and second-year English syllabus of secondary education in Spain. Two didactic units were developed for each structure, one based on the CA and the other building on Leonardi’s (The Role of Pedagogical Translation in Second Language Acquisition.Peter Lang, 2010) PT framework. Three secondary schools in Spain participated in the study with a total of 211 pupils. Statistical analysis of quantitative data complemented by a qualitative approach based on error analysis revealed that PT is as effective as CA in terms of the acquisition of the grammar topics studied by Spanish early-stage learners of English.
Capítulos en libros